Perceptions of ADHD Students on the Use of Video in Learning English Vocabulary - Fairuzah Ula Huruma (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores how students with Attention Deficit Hyperactivity Disorder (ADHD) perceive the use of video media in learning English vocabulary. The research was prompted by the need for engaging and multisensory instructional tools to help ADHD students overcome attention barriers in language acquisition. Using a qualitative descriptive design, data were collected through observations and semi-structured interviews in a specialized education school in Sidoarjo. The findings revealed that: (1) Cognitively, students perceived video as a helpful tool that clarifies word meanings through visual-auditory cues, making vocabulary easier to remember; (2) Affectively, students expressed positive feelings, noting that video media makes lessons more enjoyable and significantly reduces learning anxiety; and (3) Conatively, students showed an increased willingness to participate in classroom activities and a desire for future video-based lessons. However, this study has limitations, primarily due to the small number of participants and the specific focus on vocabulary alone, which may not represent the perceptions of ADHD students in other language skills or broader contexts. The study concludes that while video media is a highly effective tool for ADHD learners, its success is significantly influenced by structured teacher guidance. These results imply that video-based instruction is a viable strategy for enhancing vocabulary mastery in specialized educational settings.